contestada

Translate the sentence into an equation.
The sum of 9 times a number and 3 is 7.
Use the variable b for the unknown number.

Respuesta :

Answer:

9b + 3 = 7

Step-by-step explanation:

9 times a number is 9b.

The sum of 9 times a number and 3 is 9b + 3.

The sum of 9 times a number and 3 is (=) 7.     9b + 3 = 7

Answer:

9b+3=7

Step-by-step explanation:

Lets start by picking apart the sentence:

-the sum

-> we know it is going to be an addition problem

9 times a number

->we know 9 is going to be multiplied by a number(b)

and 3

->3 is going to be added to 9 and a number

is 7

->we know the sum is going to be 7

Hence, we know the equation will be:

9b+3=7

hope this helps :)